Secondary brain tumors after cranial radiation therapy: A single-institution study - Fujii, Masazumi (Rep Pract Oncol Radiother, 2020)
AIM: To study the probability of developing secondary brain tumors after cranial radiotherapy. Background Patients treated with cranial radiotherapy are at risk for developing secondary brain tumors. PATIENTS AND METHODS: We planned an institutional survey for secondary brain tumors in survivors after cranial irradiation and reviewed the 30-year duration data. Event analysis and cumulative proportion curves were performed to generally estimate the cumulative proportion of developing secondary brain tumors, cavernoma and meningioma at different periods of time. RESULTS: Secondary brain tumors occurred in 21% of cases: 10% were cavernomas, 6% were meningiomas, 3% were skull osteomas, and 1% were anaplastic astrocytoma. The cumulative proportion of developing secondary brain tumor was 6% at 10 years and 20% at 20 years, while the cumulative proportion for developing cavernomas and meningiomas was 16% and 7% at 20 years, respectively. CONCLUSION: Our study shows that patients who received cranial irradiation were at risk of secondary brain tumors such as cavernomas and meningiomas. Thus, a meticulous follow-up of cancer survivors with history of cranial irradiation by an annual MRI scan is justifiable. This will help clinicians to detect secondary brain tumors early and make its management much easier.